Black GaAs : gold-assisted chemical etching for light trapping and photon recycling - Lova, Paola (2020)
Thanks to its excellent semiconductor properties, like high charge carrier mobility and absorption coefficient in the near infrared spectral region, GaAs is the material of choice for thin film photovoltaic devices. Because of its high reflectivity, surface microstructuring is a viable approach to further enhance photon absorption of GaAs and improve photovoltaic performance. To this end, metal-assisted chemical etching represents a simple, low-cost, and easy to scale-up microstructuring method, particularly when compared to dry etching methods. In this work, we show that the etched GaAs (black GaAs) has exceptional light trapping properties inducing a 120 times lower surface reflectance than that of polished GaAs and that the structured surface favors photon recycling. As a proof of principle, we investigate photon reabsorption in hybrid GaAs:poly (3-hexylthiophene) heterointerfaces.